(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
We describe a new viverrid species (Viverra howelli n. sp.). Viverra howelli n. sp. is identified in Late Miocene (Messinian) localities in the circum Mediterranean area (Italy and Lybia) and in East Africa (Kenya). Morphologically, the new species is characterized by a relatively small size and a lower carnassial with short talonid.